2016
DOI: 10.14236/ewic/ics2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Threat Analysis of BlackEnergy Malware for Synchrophasor based Real-time Control and Monitoring in Smart Grid

Abstract: The BlackEnergy malware targeting critical infrastructures has a long history. It evolved over time from a simple DDoS platform to a quite sophisticated plug-in based malware. The plug-in architecture has a persistent malware core with easily installable attack specific modules for DDoS, spamming, info-stealing, remote access, boot-sector formatting etc. BlackEnergy has been involved in several high profile cyber physical attacks including the recent Ukraine power grid attack in December 2015. This paper inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 12 publications
0
51
0
1
Order By: Relevance
“…Back office compromise mitigations: Recently, back office has been compromised using the potential malware, e.g., BlackEnergy, as shown in [55], [98]. Such attack could affect the end-user data and normal back office operations in SG metering networks, e.g., billing, credit rating, and so on [131].…”
Section: Boc Substation Management ----mentioning
confidence: 99%
See 3 more Smart Citations
“…Back office compromise mitigations: Recently, back office has been compromised using the potential malware, e.g., BlackEnergy, as shown in [55], [98]. Such attack could affect the end-user data and normal back office operations in SG metering networks, e.g., billing, credit rating, and so on [131].…”
Section: Boc Substation Management ----mentioning
confidence: 99%
“…In order to mitigate back office threats in SG, Khan et al [98] suggested protection strategies against the back office compromise attacks with a particular focus on the BlackEnergy malware, as follows. (i) Black and white listing connections: In this, the external Internet Protocol (IP) addresses can be listed as a black-list (i.e., untrusted source) and white-list (i.e., trusted source).…”
Section: Boc Substation Management ----mentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns about vulnerabilities of other electric grids resulted. (Khan et al 2016). FERC ordered additional cyber protections for control centers duties (Order 822 2016) and future protection of cyber supply chains (Order 829 2016).…”
Section: Is There a Cost-sharing Solution?mentioning
confidence: 99%